Hadis Tentang Zakat: Analisis Komitmen Sosial dalam Baiat Jarir Bin Abdullah: The Hadith on Zakat: An Analysis of Social Commitment in the Allegiance of Jarir Bin Abdullah - Andi Wawan Mulyawan; Arifuddin Ahmad; Siti Aisyah Kara (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
This study explores the theme of zakat in the hadith of allegiance (bai‘ah) narrated by Jarir bin Abdullah r.a., aiming to understand its historical context, theological and social meanings, as well as the relevance of its teachings in contemporary Muslim society. Employing a qualitative approach through library research, this study applies thematic analysis of the hadith, focusing on asbāb al-wurūd (circumstantial context), linguistic interpretation, and socio-religious meanings. The findings reveal that zakat in Jarir’s pledge was not merely an individual obligation but also a form of social commitment that reflects the integration of devotional acts and social responsibility in Islam. In today’s context, this hadith offers a conceptual foundation for strengthening the role of zakat in addressing poverty, social inequality, and distributive justice crises. Therefore, zakat should be viewed not only as a religious ritual but also as a transformative instrument for building a just, prosperous, and inclusive society. This study emphasizes the importance of revitalizing the spirit of this hadith in modern zakat practices based on sharia principles and professional management.